Reduction of carcass weight loss in swines - Iliani PATINHO (Ciência e Tecnologia de Alimentos, 2013)
The carcass fast freezing is one of the aspects of great prominence to the final quality of pork. In order to reduce weight loss, two experiments were performed, in which the carcasses were monitored during 20 hours to evaluate the main variables involved during two different freezing processes (standard and proposed) as follows: microbiological quality, storage temperature, relative humidity (RH) and air velocity. In experiment I, the carcasses were submitted to a system using heat shock (2 hours in static tunnel at –25 °C) and subsequently sent to the equalization chamber. In experiment II, the carcasses were submitted to the heat shock and stored in a chamber with RH between 80‑85%. The chambers used in both experiments showed no change in the variables studied (internal temperature of 5 °C and air velocity of approximately 0.3 m/s). However, the relative humidity in the three chambers was evaluated and significant differences were found; as a consequence, high levels of weight loss were observed in both chambers In experiment II there was an increase of RH, which reduced the weight loss of the carcasses.